Pemanfaatan Wellbore Strengthening Agent Selama Pengeboran di Onshore Sumatera Bagian Utara Indonesia - Rasyid, Aly (Jurnal Jaring SainTek, 2019)
At northern part of Sumatera Indonesian onshore many drilling issues were encounteredin the area, in particular the overlying shales above the pay zones in the high deviatedtrajectory wells. Since the last well drilling in this area was 70’ era, so that limited data isanother drilling engineering challenge, especially to provide an accurate drilling fluid. Tocombat the drilling issues, utilization of pre-treated wellbore strengthening agent wasapplied to reduce well bore issues and strengthen the well with an effective filter cake. In Northern Sumatera Indonesian onshore well in Indonesia was used as a case study. First a brief understanding and fundamentals of geo-mechanics is described in reference to wellconstruction as well as filter cake fundamental to protect the hole stability. Results,observations and conclusions were drawn upon using a case study comparing a well ononshore in Indonesia which had many drilling problems such as stuck pipe/differentialsticking and washouts/hole enlargement issues related to well bore stability, after using thewellbore stability agent, the problems that encountered significantly decrease.